2008
DOI: 10.1002/cncr.23689
|View full text |Cite
|
Sign up to set email alerts
|

Serum HER‐2/neu and relative resistance to trastuzumab‐based therapy in patients with metastatic breast cancer

Abstract: BACKGROUND.Previous reports based on small patient numbers suggested that changes in serum HER‐2/neu levels may predict response or lack of response to trastuzumab‐based therapies in metastatic breast cancer (MBC). The objectives of this study were to pool data from 307 patients with MBC from 7 medical institutions to validate that the serum HER‐2/neu profile predicts patient resistance to trastuzumab and to establish a clinically relevant cutoff.METHODS.This was an international, multicenter, retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 75 publications
3
54
0
Order By: Relevance
“…An elevated serum HER-2/neu level as measured after 2 months of chemotherapy treatment was significantly associated with reduced long term clinical benefit. Serum HER-2/neu was also found to predict response to trastuzumab-based therapies as individuals who did not achieve a significant decline in serum HER-2/neu levels had decreased benefit from trastuzumab-based therapy (169). Many of these findings need confirmation in other independent cohorts; however, overall, they seem promising.…”
Section: Current Status Of Clinical Biomarker Discoverymentioning
confidence: 65%
“…An elevated serum HER-2/neu level as measured after 2 months of chemotherapy treatment was significantly associated with reduced long term clinical benefit. Serum HER-2/neu was also found to predict response to trastuzumab-based therapies as individuals who did not achieve a significant decline in serum HER-2/neu levels had decreased benefit from trastuzumab-based therapy (169). Many of these findings need confirmation in other independent cohorts; however, overall, they seem promising.…”
Section: Current Status Of Clinical Biomarker Discoverymentioning
confidence: 65%
“…In metastatic breast cancer, no clear relationship was found between baseline sHER2 levels and tumor response to trastuzumab-based treatment in a recently published metaanalysis [33], while other groups have suggested a role of sHER2 determination [21,34] so that no definitive conclusions can be drawn [26]. There is limited information regarding sHER2 to predict benefit from trastuzumab treatment in primary breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Receiver operating characteristic (ROC) curve analysis was performed to determine an optimal sHER2 decline during NT corresponding to pCR. A decrease of sHER2 levels of more than 20 percent during NT was regarded as significant in the following analysis (sensitivity 75%, specificity 55%) [21].…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…In a pooled analysis of 307 patients with metastatic breast cancer, individuals who did not achieve a significant decline (20%) in serum HER2/neu levels were seen to benefit less from trastuzumab-based therapy with or without chemotherapy. A reduction of 20% or more in the serum concentration of the HER2 extracellular domain was associated with increased progression-free and overall survival as compared with patients in whom a less strong reduction was observed (Serum HER2/neu and relative resistance to trastuzumab-based therapy in patients with metastatic breast cancer) [5]. In addition, based on an in vitro study using HER2-overexpressing breast tumor cells, Zabrecky et al, suggested that an extracellular domain can link to antibodies (e.g.…”
Section: Extracellular Receptor Cleavage (Receptor Shedding)mentioning
confidence: 93%